Batteries: Predicting Calendar Aging in Lithium Metal Secondary Batteries: The Impacts of Solid Electrolyte Interphase Composition and Stability (Adv. Energy Mater. 26/2018). Issue 26 (14th September 2018) - Wood, Sean M.; Fang, Chengcheng; Dufek, Eric J.; Nagpure, Shrikant C.; Sazhin, Sergiy V.; Liaw, Boryann; Meng, Y. Shirley
Abstract : In article number1801427, Eric J. Dufek and co‐workers report a means to analyze the calendar life of Li metal cells based on characterization of solid electrolyte formation and composition. By modifying the electrolyte composition, the nature of the SEI transitions from more organic in structure to more inorganic. This transition extends calendar life by 5x due to enhanced stability.